2010
DOI: 10.1007/s10585-010-9306-3
|View full text |Cite
|
Sign up to set email alerts
|

FAK is involved in invasion and metastasis of hepatocellular carcinoma

Abstract: Studies have shown that focal adhesion kinase (FAK) is overexpressed in several human tumors and plays an important role in tumor progression. However, the role and underlying mechanisms of FAK in hepatocellular carcinoma (HCC) progression remains to be elucidated. In this study, we examined FAK and phosphorylated FAK Tyr397 expression in a large series of HCCs. We found that both FAK and phosphorylated FAK Tyr397 were overexpressed in HCC samples and HCC cell lines. Increased FAK and phosphorylated FAK Tyr397… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
94
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 39 publications
5
94
0
Order By: Relevance
“…FAK/Akt signaling is known to be activated by secreted MMP-2 and MMP-9. [30][31][32][33] Our studies showed that the phosphorylation of FAK is significantly affected only by g-CCN3 and is slightly increased by ng-CCN3 after 8 h of CCN3 treatment (Fig. 7A).…”
Section: Ccn1 and Ccn3 Increase The Migration Of Sghpl-5 Trophoblast mentioning
confidence: 68%
“…FAK/Akt signaling is known to be activated by secreted MMP-2 and MMP-9. [30][31][32][33] Our studies showed that the phosphorylation of FAK is significantly affected only by g-CCN3 and is slightly increased by ng-CCN3 after 8 h of CCN3 treatment (Fig. 7A).…”
Section: Ccn1 and Ccn3 Increase The Migration Of Sghpl-5 Trophoblast mentioning
confidence: 68%
“…As a matter of fact, in response to cellular stresses, Mfn2 are involved in the regulation of cell fate through a various of pathways, including the phosphatidylinositol 3-kinase (PI3K)-Akt signaling pathway, cytokine-cytokine receptor interaction, and focal adhesion. [54][55][56] A recent study suggested that the overexpression of Mfn2 suppressed cancer progression through inhibition of Akt signaling. 24) Furthermore, bavachin was reported to exhibit direct effect on Akt phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, talin-1 also functions in signal transduction in focal adhesions, as it recruits focal adhesion kinase (FAK), which in turn recruits Src and Ras to activate downstream signaling pathways [22]. It is noteworthy that FAK itself is involved in the metastasis and invasion of HCC [23]. Recently, several molecular-targeted therapies have been developed for the treatment of various malignant diseases, and the multikinase inhibitor sorafenib has shown survival benefits in patients with advanced HCC [24].…”
Section: Discussionmentioning
confidence: 99%